حفظ القلب: مقصد مُكَمِّل في إطار مقاصد الشريعة الإسلامية: A Complementary Maqāṣid in the Framework of Islamic Sharīʿah Objectives - Ahmed AL-Melahi, Abdellah Ali (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يهدف هذا البحث إلى إثبات مشروعية اعتبار "حفظ القلب" مقصدًا شرعيًا إضافيًا سادسًا ضمن الضروريات في مقاصد الشريعة الإسلامية والتي هي: حفظ الدين، وحفظ النفس، وحفظ العقل، وحفظ النسل، وحفظ المال. ينطلق البحث من إشكالية رئيسية تتعلق بإمكانية تصنيف "حفظ القلب" كمقصد كلي في الشريعة، مع بيان أثره في تعزيز المقاصد الأخرى، وتوضيح الأبعاد الفردية، والأسرية، والاجتماعية المرتبطة به. لتحقيق هذا الهدف، استخدم البحث منهجية استقرائية بتحليل النصوص القرآنية والأحاديث النبوية التي تؤكد أهمية القلب كمركز للإيمان والأخلاق، مع توظيف المنهج التحليلي والمقارن لبيان العلاقة بين "حفظ القلب" والمقاصد الخمسة الأخرى. توصل البحث إلى عدة نتائج مهمة، من أبرزها أن "حفظ القلب" هو مقصد شرعي أصيل تدعمه النصوص الشرعية، مثل قوله تعالى "إِلَّا مَنْ أَتَى اللَّهَ بِقَلْبٍ سَلِيمٍ" (الشعراء:89)، وحديث النبي ﷺ: "ألا وإن في الجسد مضغة إذا صلحت صلح الجسد كله" (البخاري، 1987، ومسلم، 2000). كما أثبت البحث أن "حفظ القلب" يعزز المقاصد الأخرى، حيث يسهم في حفظ الدين (بالإخلاص)، وحفظ النفس (بالتخلص من الحقد والغضب)، وحفظ العقل (بالوقاية من الشبهات)، وحفظ النسل (بتنقية القلب من الشهوات)، وحفظ المال (بالابتعاد عن الجشع والطمع). خلص البحث إلى أن "حفظ القلب" ليس مقصدًا فرعيًا بل مقصد كلي، حيث إن إصلاح القلب يؤدي إلى صلاح الفرد والأسرة والمجتمع. وأوصى البحث بإدراج "حفظ القلب" ضمن مقاصد الشريعة، مع تعزيز حضوره في المناهج التربوية والخطاب الديني، ودعا إلى مزيد من الدراسات التطبيقية حول كيفية تفعيل هذا المقصد في الفقه والاجتهاد الشرعي. ABSTRACT This research aims to establish the legitimacy of considering Preserving the Heart "Ḥifẓ al-Qalb" as an independent objective within the overarching objectives of Islamic Sharī’ah, alongside the five well-known objectives: preserving religion, life, intellect, lineage, and wealth. The research addresses a central issue concerning the possibility of classifying "Preserving the Heart" as a comprehensive Sharī’ah objective. It further explores its impact on enhancing the other Sharī’ah objectives and highlights its implications on the individual, family, and societal levels. To achieve this goal, the research employed an inductive methodology by analyzing Quranic verses and Prophetic Hadiths that emphasize the significance of the heart as the centre of faith and morality. The research also utilized analytical and comparative approaches to demonstrate the relationship between "Preserving the Heart" and the five established objectives of Sharī’ah. The research reached several key conclusions, most notably that "Preserving the Heart" is a legitimate and independent Sharī’ah objective, supported by explicit textual evidence. This includes Allah’s statement: “Except for he who comes to Allah with a sound heart” (Quran, 26:89) and the Prophet Muhammad’s ﷺ saying: “Verily, there is a piece of flesh in the body which, if it is sound, the entire body is sound, and if it is corrupt, the entire body is corrupt — truly it is the heart” (Al-Bukhārī, 1987 & Muslim, 2000). The study further proved that "Preserving the Heart" supports the five key Sharī’ah objectives by strengthening the preservation of religion (through sincerity), preserving life (by eliminating hatred and anger), preserving intellect (by safeguarding it from doubts), preserving lineage (by protecting the heart from desires), and preserving wealth (by curbing greed and avarice). The research concluded that "Preserving the Heart" is not a subsidiary objective but a comprehensive and independent Sharī’ah objective. It emphasized that the purification of the heart leads to the rectification of the individual, family, and society as a whole. The study recommended the inclusion of "Preserving the Heart" as one of the higher objectives of Sharī’ah, the integration of its principles into educational curricula and religious discourse, and called for further applied research on how this objective can be activated within Islamic jurisprudence and contemporary Sharī’ah -based rulings.